2019
DOI: 10.1016/j.apenergy.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moderate thermal environments on cognitive performance: A multidisciplinary review

Abstract: The effect of the thermal environment on performance and productivity has been a focus of interest among indoor environmental researchers for nearly a century, but most of that work has been conducted in relative isolation from the cognate disciplines of human performance evaluation. The present review examines thermal environmental effects on cognitive performance research conducted across multiple disciplines. After differentiating performance from productivity, we compare the two dominant conceptual models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(67 citation statements)
references
References 196 publications
(378 reference statements)
5
56
1
Order By: Relevance
“…49 Performance during the finger-tapping test was stable over a specific exposure range likely due to no significant clothing and temperature differences observed at 26°C and 36°C. As indicated in previous research, 4,38,50 the lower motor performance at 16°C in contrast to 26°C and 36°C suggests that cold exposure could undermine manual motor performance. This could be attributed to low skin and tendon temperatures and slow muscle conduction velocity in cold environments.…”
Section: Pre-room: Nssupporting
confidence: 61%
See 2 more Smart Citations
“…49 Performance during the finger-tapping test was stable over a specific exposure range likely due to no significant clothing and temperature differences observed at 26°C and 36°C. As indicated in previous research, 4,38,50 the lower motor performance at 16°C in contrast to 26°C and 36°C suggests that cold exposure could undermine manual motor performance. This could be attributed to low skin and tendon temperatures and slow muscle conduction velocity in cold environments.…”
Section: Pre-room: Nssupporting
confidence: 61%
“…high body temperatures (Figures 7and 8) in hot environments. 4,45 Additionally, the results of this study indicated that wearing fewer clothing items had a tendency to increase the sustained attention levels, especially in cold environments. This could be attributed to the significant difference in attention levels between the 0.3 clo and 0.9 clo conditions, with higher performance at 0.3 clo.…”
Section: Pre-room: Nsmentioning
confidence: 67%
See 1 more Smart Citation
“…Some studies found that moderately higher temperatures incurred significantly reduced cognitive performance [103]. However, the effect of moderate heat stress on cognitive performance is still controversial [104]. Therefore, we cannot conclude that the visual connection through a window has a positive impact on the various cognitive abilities of the occupants of the space, but it does enhance the working memory and concentration.…”
Section: Effects Of the Outdoor View From The Window On Cognitive Permentioning
confidence: 85%
“…While some studies document direct linkages of temperature and self-reported performance at work [34][35][36], there is still disagreement about "ideal" set-points. Some authors suggest lower temperatures to address distraction and complaints [37] while others make the case in favor of warmer indoors, without losses on reported perceived productivity [38,39]. The other dimension that has been studied was "ventilation rate" (i.e., supply of outdoor air) due to its indirect influence on workers' performance, caused by the impact of ventilation on thermal comfort, air quality, and concentration of indoor generated pollutants [40,41].…”
Section: Introductionmentioning
confidence: 99%